The Role of Competitive Advantage in Mediating the Influence of Customer Relationship Marketing on Marketing Performance at Atanaya Kuta Bali - Widhya Pibriari, Ni Putu; Nugraha, Surya (Jurnal Manajemen Pelayanan Hotel, 2024)
This research aims to analyze the influence of customer relationship marketing on marketing performance, analyze the influence of customer relationship marketing on competitive advantage, analyze the influence of competitive advantage on marketing performance, and analyze the role of competitive advantage in mediating the influence of customer relationship marketing on marketing performance. The sampling technique uses a purposive sampling method. The population in this study was 72 employees at Atanaya Kuta Bali and 53 people were used as respondents using a purposive sampling technique, selecting samples using certain criteria. The type of data used in this research is quantitative data. The data source in this research is primary data. Data analysis in this research uses the Partial Least Square (PLS) approach using SmartPLS software, namely SmartPLS 3.2.7. The research results show that, 1) customer relationship marketing has a positive and significant effect on marketing performance, 2) customer relationship marketing has a positive and significant effect on competitive advantage, 3) competitive advantage has a positive and significant effect on marketing performance, and 4) competitive advantage is able to mediate the influence of customer relationship marketing on marketing performance. These results indicate that customer relationship marketing has an influence on marketing performance. This shows that to improve marketing performance, management at Atanaya Kuta Bali should maximize customer relationship marketing Keywords: Competitive Advantage, Customer Relationship Marketing, Marketing Performance